Improved effect of fresh ginseng paste (radix ginseng-ziziphus jujube) on hyperuricemia based on network pharmacology and molecular docking - Zhang, Hao; Liu, Wei; Qi, Si-Min; Chi, Jian-Feng; Gao, Qiang; Lin, Xiang-Hui; Ren, Shen; Wang, Zi; Lei, Xiu-juan; Li, Wei (Frontiers in Pharmacology, 2022)
Background: Hyperuricemia (HUA) is a metabolic disease caused by reduced excretion or increased production of uric acid. This research aims to study the practical components, active targets, and potential mechanism of the “Radix ginseng (RG)-Ziziphus jujube (ZJ)” herb pair through molecular docking, network pharmacology, and animal experiments. Methods: The potential targets of “Radix ginseng (RG)-Ziziphus jujube (ZJ)” herb pair were obtained from the TCMSP database. The therapeutic targets of HUA were acquired from the GendCards, OMIM, PharmGkb, and TTD databases. Protein-protein interaction network (PPI) was constructed in the STRING 11.0 database. The David database was used for enrichment analysis. Molecular Docking was finished by the AutoDock Vina. And we employed Radix ginseng and Ziziphus jujube as raw materials, which would develop a new functional food fresh ginseng paste (FGP) after boiling. In addition, benzbromarone (Ben) (7.8 mg/kg) and allopurinol (All) (5 mg/kg) were used as positive drugs to evaluate the hyperuricemia induced by FGP (400 and 800 mg/kg) potassium oxazine (PO) (100 mg/kg) and hypoxanthine (HX) (500 mg/kg) on mice. Results: The results showed that 25 targets in the “RG-ZJ” herb pair interacted with hyperuricemia. Then protein-protein interaction (PPI) analysis showed that TNF, IL-1β, and VEGFA were core genes. KEGG enrichment analysis showed that the Toll-like receptor signaling pathway and IL-17 signaling pathway were mainly involved. Meantime, animal experiments showed that FGP could improve the HUA status of mice by reducing serum UA BUN, XO, and liver XO levels (p < 0.05, p < 0.01). Furthermore, we analyzed the main ingredients of FGP by HPLC. We found that the main ingredients of FGP had solid binding activity to the core target of HUA by molecular docking. Conclusion: This study explored the active ingredients and targets of the “RG-ZJ” herb pair on HUA through network pharmacology, molecular docking, and animal experiments. It revealed the improvement of FGP in mice with HUA.